PENERAPAN MODEL GUIDED INQUIRY LEARNING DIPADU DENGAN CONCEPT MAP UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR ANALITIS SISWA KELAS X-6 SMA NEGERI KEBAKKRAMAT - Setya Maulani; Murni Ramli; Dewi Puspita Sari; Priyadi Dwi Parwanto (Universitas Sebelas Maret, 2016)
The purpose of this research is to increase the analytical thinking of X-6 students of SMA Negeri Kebakkramat by using guided inquiry learning model combined with concept map. This research is classroom action research execute in 3 cycles. Each cycles consist of 4 stages, the 4 stages is scheming, implementation, observation and reflection. The procedure of this research use Kemmis and Mc Taggart method. The subject of this research is X-6 students of SMA Negeri Kebakkramat school year 20014/2015 which amounts to 34 students consist 8 boys students and 26 girls students. This data of this research be obtained by using analytical thinking observation method, analytical thinking test, interview and documentation.This results of this research by using guided inquiry learning combined with concept map shows increase analytical thinking X-6 students of SMA Negeri Kebakramat from pra cycle, cycle I, cycle II and cycle III. The overall score the analytical thinking increase from 4,88 (40,69%) become 7,31 (60,91%). Differentiating aspect increase from 1,32 (47,79%) become 2,28 (56,99%), organizing aspect increase from 1,91 (47,79%) become 2,87 (71,69%) and attributing aspect increase from 1,65 (41,18%) become 2,16 (54,04%). Based on result of this research by using guided inquiry learning combined with concept map can increase the analytical thinking of X-6 students SMA Negeri Kebakkramat. Keywords: guided inquiry learning, concept map, analytical thinking ability